The Effect Of Delaying Umbilical Cord Cutting On Hemoglobin Levels In Newborn Babies - Restya, Erda Restya; Lailaturohmag, Laila; Lukmawati, Dwi; Septiana, Fransiska (Health Gate, 2024)
AbstractIron deficiency anemia, commonly occurring in infants aged 6-24 months, can be prevented by delaying the cutting of the umbilical cord after birth. A quasi-experimental study conducted at the Mother and Child Clinic in Mojo Kediri involved 30 infants, divided into an experimental group (with delayed cord clamping) and a control group. Hemoglobin levels were measured using a Hematology Autoanalyzer, and the data were analyzed using a t-test. The intervention group, with a delay in cord clamping for 1 hour, showed an average increase in Hb levels from 15.444 g/dl to 19.800 g/dl after 24 hours. Meanwhile, the control group, without any delay, increased from 15.544 g/dl to 16.844 g/dl. Delaying the umbilical cord clamping significantly increased hemoglobin levels in newborns (p-value: 0.000). Infants with delayed cord clamping exhibited higher hemoglobin levels, better body iron reserves, and reduced risk of anemia. The higher red blood cell levels supported better cardiopulmonary adaptation and increased breastfeeding duration in early life. The research concludes that delaying the cutting of the umbilical cord for 2 minutes in newborns can enhance Hb levels after 24 hours compared to cord clamping at 15 seconds after birth. This highlights the importance of delaying cord clamping to support hemoglobin health and infant development.Keywords: Delaying Umbilical Cord Clamping, Hemoglobin Levels, Newborns